The dynamics of trade and competition - Natalie Chen; Jean Imbs; Andrew Scott (National Bank of Belgium, 2006)
We present, extend and estimate a model of international trade with firm heterogeneity in the tradition of Melitz (2003) and Melitz and Ottaviano (2005). The model is constructed to yield testable implications for the dynamics of international prices, productivity levels and markups as functions of openness to trade at a sectoral level. The theory lends itself naturally to a difference in differences estimation, with international differences in trade openness at the sector level reflecting international differences in the competitive structure of markets. Predictions are derived for the effects of both domestic and foreign openness on each economy. Using disaggregated data for EU manufacturing over the period 1989-1999 we find evidence that trade openness exerts a competitive effect, with prices and markups falling and productivity rising. Consistent with theory however, these effects diminish and may even revert in the longer term as less competitive economies become attractive havens from which to export from. We provide evidence that this entry into less open economies induces pro-competitive effects overseas in response to domestic trade liberalization.
Keywords: E31; F12; F15; L16; 330; Competition; Globalization; Markups; Openness; Prices; Productivity; Trade; Internationaler Wettbewerb; Globalisierung; Mark-up Pricing; Außenwirtschaftstheorie; Schätzung; Industrie; EU-Staaten